Cyano-substituted triptycene-based monolayers on Au(111): tripodal adsorption, dipole engineering, and charge transfer - Das, Saunak; Asyuda, Andika; Shoji, Yoshiaki; Kosaka, Atsuko; Fukushima, Takanori; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2021)
Molecules with tripodal anchoring groups are generally capable of forming self-assembled monolayers (SAMs), which, however, frequently suffer from inhomogeneous bonding configurations and limited quality. A suitable platform to avoid these problems are triptycenes, which can be decorated with three substrate-specific anchoring groups and substituted with one or three functional tail groups. Along these lines, selecting thiol and cyano groups as the anchoring and tail functionalities, respectively, we synthesized 1,8,13-tricyano-4,5,16-trimercaptotriptycene and fabricated the respective SAMs on Au(111). These SAMs exhibit dense molecular packing and nearly perfect tridentate adsorption configuration, with bonding of all three thiolate groups to the substrate. Due to such a packing, the density of functional tail groups in these SAMs is close to that in the analogous monodentate monolayers, with a similar electrostatic effect for polar cyano groups but better robustness provided by the tripodal anchoring. The electronic communication between the tail groups and the substrate occurs through individual blades of the adsorbed molecules and is hardly affected by the presence of the aliphatic bridge connecting these blades, as verified by the measurements of electron transfer dynamics. Three parallel charge transport channels enable efficient electronic coupling to the substrate, representing an additional advantage of the triptycene-based SAMs for applications.